Activation of EP4 alleviates AKI-to-CKD transition through inducing CPT2-mediated lipophagy in renal macrophages - Guan, Xu; Liu, Yong; Xin, Wang; Qin, Shaozong; Gong, Shuiqin; Xiao, Tangli; Zhang, Daohai; Li, Yan; Xiong, Jiachuan; Yang, Ke; He, Ting; Zhao, Jinghong; et al. (Frontiers in Pharmacology, 2022)
Acute kidney injury (AKI) is a common clinical syndrome with complex pathogenesis, characterized by a rapid decline in kidney function in the short term. Worse still, the incomplete recovery from AKI increases the risk of progression to chronic kidney disease (CKD). However, the pathogenesis and underlying mechanism remain largely unknown. Macrophages play an important role during kidney injury and tissue repair, but its role in AKI-to-CKD transition remains elusive. Herein, single nucleus RNA sequencing (snRNA-Seq) and flow cytometry validations showed that E-type prostaglandin receptor 4 (EP4) was selectively activated in renal macrophages, rather than proximal tubules, in ischemia-reperfusion injury (IRI)-induced AKI-to-CKD transition mouse model. EP4 inhibition aggravated AKI-to-CKD transition, while EP4 activation impeded the progression of AKI to CKD though regulating macrophage polarization. Mechanistically, network pharmacological analysis and subsequent experimental verifications revealed that the activated EP4 inhibited macrophage polarization through inducing Carnitine palmitoyltransferase 2 (CPT2)-mediated lipophagy in macrophages. Further, CPT2 inhibition abrogated the protective effect of EP4 on AKI-to-CKD transition. Taken together, our findings demonstrate that EP4-CPT2 signaling-mediated lipophagy in macrophages plays a pivotal role in the transition of AKI to CKD and targeting EP4-CPT2 axis could serve as a promising therapeutic approach for retarding AKI and its progression to CKD.